Intelligent Healthcare Ecosystem: The Convergence of AI Agents, Clinical Expertise, and Patient Care - Ravindra Reddy Madireddy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of Agentic Process Automation (APA) in healthcare represents a revolutionary approach to addressing industry challenges through intelligent, semi-autonomous systems. This comprehensive article examines how APA transcends traditional automation by leveraging advanced artificial intelligence capabilities to transform both administrative and clinical processes. The article explores APA's applications across electronic health record management, patient scheduling, insurance processing, compliance monitoring, diagnostic assistance, treatment planning, predictive analytics, and real-time monitoring. Implementation strategies, challenges, and outcomes are thoroughly evaluated, highlighting significant improvements in efficiency, patient satisfaction, clinical outcomes, and cost-effectiveness. The article further explores emerging technologies integrating with APA and provides strategic recommendations for healthcare organizations navigating this technological evolution. This article demonstrates how APA serves as a cornerstone for developing intelligent healthcare ecosystems that optimize both individual patient care and system-level performance while advancing the quadruple aim of healthcare.
Keywords: Healthcare Automation; Artificial Intelligence; Clinical Decision Support; Administrative Efficiency; Intelligent Healthcare Systems